2009
DOI: 10.1371/journal.pone.0004728
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MMP7 and Its Cross-Talk with the FAS/FASL System during the Acquisition of Chemoresistance to Oxaliplatin

Abstract: BackgroundThe efficacy of oxaliplatin in cancer chemotherapy is limited by the development of drug resistance. MMP7 has been related to the loss of tumor cell response to cytotoxic agents although the exact mechanism is not fully understood. Moreover, MMP7 is an independent prognosis factor for survival in patients with colorectal cancer. The aim of the present study was to analyze the role of MMP7 and its cross-talk with the Fas/FasL system during the acquisition of oxaliplatin resistance in colon cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 30 publications
5
78
0
Order By: Relevance
“…Our data suggest that MMPs are involved in the development of stroma-induced resistance to EGFR-targeted therapies. Furthermore, previous studies have indicated a correlation between MMPs and the resistance to cytotoxic agents (44)(45)(46). Thus, when Figure 6.…”
Section: Discussionmentioning
confidence: 94%
“…Our data suggest that MMPs are involved in the development of stroma-induced resistance to EGFR-targeted therapies. Furthermore, previous studies have indicated a correlation between MMPs and the resistance to cytotoxic agents (44)(45)(46). Thus, when Figure 6.…”
Section: Discussionmentioning
confidence: 94%
“…Impairment of this pathway promotes oxaliplatin resistance as it was demonstrated by Almendro and colleagues. In their work, overexpression of MMP7 is associated with oxaliplatin resistance acquisition and its genetic silencing restores oxaliplatin sensitivity by increasing the Fas receptor (71). Later on, they demonstrated how cells with acquired resistance to oxaliplatin displayed mesenchymal characteristics that were enhanced by CD95 triggering, after oxaliplatin treatment, contributing to a metastatic phenotype (72).…”
Section: Apoptosismentioning
confidence: 99%
“…MMP-7 also causes a decrease of FAS at the cell surface, which leads to oxaliplatin-resistance in colon cancer cells [86]. Although MMP-7 cleaves FASL and induces apoptosis, constitutive expression of matrilysin may select for cells with reduced sensitivity to Fas-mediated apoptosis and renders cancer cells more invasive [87].…”
Section: Regulation Of Cell Survivalmentioning
confidence: 99%